Identification of circulating plasma ceramides as a potential sexually dimorphic biomarker of pancreatic cancer‐induced cachexia - Jeffery M. Chakedis; Mary E. Dillhoff; Carl R. Schmidt; Priyani V. Rajasekera; David C. Evans; Terence M. Williams; Denis C. Guttridge; Erin E. Talbert (JCSM Rapid Communications, 2022)
Abstract Background Cancer patients who exhibit cachexia lose weight and have low treatment tolerance and poor outcomes compared with cancer patients without weight loss. Despite the clear increased risk for patients, diagnosing cachexia still often relies on self‐reported weight loss. A reliable biomarker to identify patients with cancer cachexia would be a valuable tool to improve clinical decision making and identification of patients at risk of adverse outcomes. Methods Targeted metabolomics, which included panels of amino acids, tricarboxylic acids, fatty acids, acylcarnitines, and sphingolipids, were conducted on plasma samples from patients with confirmed pancreatic ductal adenocarcinoma (PDAC) with and without cachexia and control patients without cancer (n = 10/group, equally divided by sex). Additional patient samples were analysed (total n = 95), and receiver operating characteristic (ROC) analyses were performed to establish if any metabolite could effectively serve as a biomarker of cachexia. Results Targeted profiling revealed that cachectic patients had decreased circulating levels of three sphingolipids compared with either non‐cachectic PDAC patients or patients without cancer. The ratio of C18‐ceramide to C24‐ceramide (C18:C24) outperformed a number of other previously proposed biomarkers of cachexia (area under ROC = 0.810). It was notable that some biomarkers, including C18:C24, were only altered in cachectic males. Conclusions Our findings identify C18:C24 as a potentially new biomarker of PDAC‐induced cachexia that also highlight a previously unappreciated sexual dimorphism in cancer cachexia.